2022
DOI: 10.3390/ijerph19021008
|View full text |Cite
|
Sign up to set email alerts
|

The Lived Experiences of Fathers in Mealtimes: A Thematic Synthesis of Qualitative Literature

Abstract: The paternal experience of family mealtimes is an emerging field within qualitative literature. Previous quantitative studies suggest that differences exist between fathers’ and mothers’ mealtime behaviours, particularly in response to fussy eating. However, qualitative research has not yet focused exclusively on fathers’ fussy eating experiences. This metasynthesis aimed to provide insights into the general paternal experience, inclusive of their fussy eating responses. Thematic synthesis methodology was adop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…This led to a vicious cycle of increased caregiver anxiety and behaviour problems from the children. These findings are also echoed in other studies which reported a bidirectional pattern between negative parental emotional states and disruptive mealtime behaviours in children 5 8 9…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…This led to a vicious cycle of increased caregiver anxiety and behaviour problems from the children. These findings are also echoed in other studies which reported a bidirectional pattern between negative parental emotional states and disruptive mealtime behaviours in children 5 8 9…”
Section: Discussionsupporting
confidence: 80%
“…This finding is similar to a thematic synthesis that reported parents using preferred food like desserts to reinforce the consumption of routine meals. They also identified various studies where parents reported technology-based distractions as a barrier to the mealtime experience 5. Conversely, studies have also reported caregivers employing inventive, child-specific strategies to promote feeding behaviour 11.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations